2020
DOI: 10.1002/rcm.8623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic removal techniques prior to carbonate stable isotope analysis of lacustrine marls: A case study from palaeo‐lake Fucino (central Italy)

Abstract: Rationale The suitability of organic matter (OM) removal pre‐treatments in isotopic studies of lacustrine carbonates is currently under debate. Naturally occurring OM seems to have a negligible effect on the bulk isotopic composition of carbonates compared with changes induced by pre‐treatments. This study provides further insights into the possible effects induced by commonly used pre‐treatments on natural lacustrine carbonates. Methods Sixteen samples from the Fucino F1–F3 lacustrine succession (Abruzzo, cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…(2013) and Mannella et al . (2020). The isotopic ratios are reported in the well‐known δ‐notation ‰ (per mill).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) and Mannella et al . (2020). The isotopic ratios are reported in the well‐known δ‐notation ‰ (per mill).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the high ratio between carbonate content and organic matter (total inorganic carbon/total organic carbon, i.e. TIC/TOC: 0.96 ± 0.61), no pretreatment was performed to remove sedimentary organic matter, following the general results of Wierzbowski (2007), Oehlerich et al (2013) and Mannella et al (2020). The isotopic ratios are reported in the well-known δ-notation ‰ (per mill).…”
Section: Methodsmentioning
confidence: 99%
“…Bulk sediment samples were treated with Clorox to remove organic material (Mannella et al, 2020), and then sieved through a 125-µm mesh to remove shell material and isolate the fine endogenic fraction, which was then analysed using a ThermoFinnegan Delta Plus XP mass spectrometer connected to a GasBench. Results are reported in standard delta notation relative to VPDB with analytical precision of ±0.08‰ (1σ).…”
Section: Lake Sedimentsmentioning
confidence: 99%
“…Chemical cleaning of carbonate skeletons prior to chemical analysis and both improvement of the data quality and potential artefacts associated with this are widely discussed in the literature (Barker et al, 2003;Holcomb et al, 2015;Loxton et al, 2017), but a plausible pre-treatment method for the removal of organics still needs to be found (Inoue et al, 2004). Mannella et al (2020) showed that the suitability of chemical pre-treatments for organic matter removal from carbonate matrices should be evaluated on a case-by-case basis and, in case of relatively low organic content, should be avoided. In addition to CaCO 3 crystal lattice, shells of barnacles and bivalves usually contain up to 5 % of organic matter (Bourget, 1987;Wolowicz and Goulletquer, 1999;Marin and Luquet, 2004;Rueda and Smaal, 2004).…”
Section: Caco 3 Polymorph Type and Elemental Concentrationsmentioning
confidence: 99%
“…In the last few decades, increasing attention has been paid to the relationship between the composition of shells and external environmental factors. It has been repeatedly observed that the mineral type and accumulated trace element concentrations in CaCO 3 shells of marine invertebrates are integrated records of environmental conditions (Marchitto et al, 2000;Rodland et al, 2006). The elemental composition of the carbonate skeleton can provide records of seawater chemistry and has a significant potential for the fields of palaeoceanography and palaeoclimatology (Freitas et al, 2006;Gillikin et al, 2006;Khim et al, 2003;Ponnurangam et al, 2016;Vander Putten et al, 2000).…”
Section: Introductionmentioning
confidence: 99%